The International Olympic Committee (IOC) Consensus Statement on periodic health evaluation of elite athletes, March 2009 - Ljungqvist, A.; Jenoure, P. J.; Engebretsen, L.; Alonso, J. M.; Bahr, R.; Clough, A. F.; de Bondt, G.; Dvorak, J.; Maloley, R.; Matheson, G.; Meeuwisse, W.; Meijboom, E. J.; et al. (British Journal of Sports Medicine, 2009)
The Olympic Games is the largest sport event in the world. In Beijing, 10 500 athletes competed, selected from a large group of elite athletes in 204 countries. Sports participation on the elite level, aside from winning medals, fame and other rewards, is also important from a health perspective. There is no longer any doubt that regular physical activity reduces the risk of premature mortality in general, and of coronary heart disease, hypertension, colon cancer, obesity and diabetes mellitus in particular. The question is whether the health benefits of sports participation outweigh the risk of injury and long-term disability, especially in high-level athletes. Sarna et al have studied the incidence of chronic disease and life expectancy of former male world-class athletes from Finland in endurance sports, power sports and team sports. The overall life expectancy was longer in the high-level athlete compared with a reference group (75.6 vs 69.9 ). (s.a. http://doi.org/10.1097/JSM.0b013e3181b7332c)